Sulfamic acid catalyzed synthesis of new 3, 5-[(sub)phenyl]-1H-pyrazole bearing N1-isonicotinoyl: And their pharmacological activity evaluation. Issue 23 (1st December 2020) - Bhirud, Jayashri D.; Patil, Rajendra D.; Narkhede, Hemant P.
Graphical abstract: A series of 3, 5-[(sub)phenyl]-1 H -pyrazole bearing N 1 -isonicotinoyl derivatives were synthesized by using sulfamic acid as a catalyst. The main advantages of the present protocol are use of sulfamic acid as inexpensive and sustainable catalyst, simple work-up procedure avoiding column chromatography, no hazardous waste, and mild reaction conditions. The synthesized compounds were screened for in vitro biological activities: antioxidant, antimicrobial, antimycobacterial and anticancer. The present study contributes to the findings and development of new pyrazole(s) derivatives which are having better pharmacological activity. Abstract: A sustainable synthesis of new 3, 5-[(sub)phenyl]-1 H -pyrazole bearing N 1 -isonicotinoyl derivatives from substituted chalcones and isoniazid by using sulfamic acid and their pharmacological activity evaluation is reported. An anti-oxidant study is performed by using DPPH assay. In vitro anti-mycobacterial activity of compounds bearing R/R′ = 4-CH3 /4-F and 3-OCH3 /4-Cl showed complete inhibition (99%) at the MIC of 31 and 34 μM respectively. Antibacterial screening of compounds bearing R/R′ = 4-CH3 /4-F; 4-OCH3 /4-Br; and 4-OCH3 /4-Cl has shown noticeable inhibition (27 mm) against Staphylococcus aureus . The anti-cancer bioassay demonstrated that the five compounds were active on human breast cancer cell line MCF-7; however on HeLa cervical cancer cells only two compounds are active in comparison to standard drug Doxorubicin. Higher inhibitory effects observed in this study appear to be dependent on the chloro, bromo, fluoro and methoxy functionality present on the aromatic nucleus. The structures of all the compounds are established using NMR ( 1 H and 13 C), FT-IR, Mass and elemental analysis.